Design and Simulation of Frequency Modulation Continuous Waveform (FMCW) For Automotive Radar Systems (International Journal of Psychosocial Rehabilitation, 2020)
Safety in car driving has become essential with the use of various radar systems. In this paper, we consider the design and simulation of Frequency Modulation Continuous Waveform (FMCW) for Automotive Radar Systems. Here the FMCW radar is demonstrated in SystemVue, which generates saw tooth waveform and frequency sweep in the 24 GHz band. Target model and clutter are set accordingly. Measurements included in this work are saw tooth waveform generation, frequency vs. time transmitted waveform, and received waveforms.